2021
DOI: 10.1080/23322373.2021.1930692
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Supplement: Advancing the practice of operations management and innovation to drive Africa forward in the era of the Fourth Industrial Revolution (4IR)

Abstract: The Fourth Industrial Revolution (4IR) is paving the way for new and disruptive approaches to managing operations, innovation, and supply chains. Africa cannot ignore this revolution and afford to stand by while the rest of the world moves forward. In this paper, I invite scholars in the broader field of operations management and innovation to take part in the dialogue, undertake research to advance Africa in the 4IR era, publish their work to ensure that what happens in Africa does not remain in Africa, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Several empirical studies have confirmed that firms' use of Fourth Industrial Revolution technologies, such as big data analytics, artificial intelligence, and cloud computing, can create new opportunities for the growth of emerging economies [47,48]. These technologies have helped firms improve their competitiveness, which is positively reflected in their organizational and innovation performance [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical studies have confirmed that firms' use of Fourth Industrial Revolution technologies, such as big data analytics, artificial intelligence, and cloud computing, can create new opportunities for the growth of emerging economies [47,48]. These technologies have helped firms improve their competitiveness, which is positively reflected in their organizational and innovation performance [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…In the ever-evolving landscape of international business, the lessons learned pave the way for future success, transforming challenges into opportunities for growth and meaningful impact. In the vast and diverse market landscape of Africa, the adoption of Big Data in Fast-Moving Consumer Goods (FMCG) supply chains is poised to revolutionize operations, bringing forth a new era of efficiency and adaptability (Nsakanda, 2021) This paper explores the potential applications for Big Data in the African FMCG sector, addressing market-specific challenges and opportunities, the adaptation of U.S. company strategies to African contexts, and showcasing case studies of early adopters leading the charge. Africa's FMCG sector, while brimming with opportunities, is not without its unique challenges.…”
Section: Navigating Uncharted Waters: Challenges and Lessons Learned ...mentioning
confidence: 99%